Effect of Wild Strains Used as Starter Cultures on Free Fatty Acid Profile of Urfa Cheese - Kirmaci H. Avni (Polish Journal of Food and Nutrition Sciences)
In the present study, the influences of wild-type lactic acid bacteria including Lactococcus lactis subsp. lactis 1B4, Lactococcus garvieae IMAU 50157, Enterococcus faecium ATCC 19434, Enterococcus durans IMAU 60200 and Enterococcus faecalis KLDSO.034 on the composition and free fatty acid contents of Urfa cheeses were evaluated throughout the ripening period. Three different combinations of the strains were employed in the manufacture of cheeses from pasteurised milk. These are: cheese A (strains 1B4+ATCC 19434+IMAU 50157), cheese B (strains 1B4+IMAU 60200+ATCC 1934) and cheese C (strains ATCC 19434+1B4+IMAU 50157+IMAU 60200+KLDSO.0341). The control cheese (cheese D) was produced from raw ewe’s milk without starter culture. The basic composition of ripened cheese samples was not significantly affected by wild type strains. C cheese had a higher level of lipolysis than the other cheeses at all stages of ripening (p<0.05). Sensory evaluation of the cheese samples revealed that control cheese had significantly higher aroma and flavour scores than the other cheeses.